1995
DOI: 10.1111/j.1476-5381.1995.tb15941.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of an endogenous 5‐HT1B‐like receptor to increases in intracellular calcium through a pertussis toxin‐sensitive mechanism in CHO‐K1 cells

Abstract: 1 Chinese hamster ovary cells (CHO-Ki) express an endogenous 5-hydroxytryptamine (5-HT),n-like receptor that is negatively coupled to adenylyl cyclase through a pertussis toxin (PIX)-sensitive mechanism. Furthermore, the human adenosine A, receptor when expressed in CHO-Ki cells (CHO-Al) has been shown to mobilize intracellular Ca2" through a PTX-sensitive mechanism. Therefore the aim of this investigation was to determine whether the endogenous 5-HTB-like receptor was 7 These data demonstrate that in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Previous studies have demonstrated that activation of both 5-HT 1B and 5-HT 1D receptors causes [Ca 2ϩ ] i elevation through the PTX-sensitive mechanism in other cells. 23,24 In this study, we have verified that activation of endogenous vascular 5-HT 1B/1D receptors by SUM and serotonin causes Ca 2ϩ mobilization and subsequent contraction through a PTX-sensitive pathway in vascular tissue preparations. Moreover, this is the first study demonstrating that activation of endogenous vascular 5-HT 1B receptors contribute to hypercontractions, concomitant with augmented Ca 2ϩ mobilization in atherosclerotic vessels.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have demonstrated that activation of both 5-HT 1B and 5-HT 1D receptors causes [Ca 2ϩ ] i elevation through the PTX-sensitive mechanism in other cells. 23,24 In this study, we have verified that activation of endogenous vascular 5-HT 1B/1D receptors by SUM and serotonin causes Ca 2ϩ mobilization and subsequent contraction through a PTX-sensitive pathway in vascular tissue preparations. Moreover, this is the first study demonstrating that activation of endogenous vascular 5-HT 1B receptors contribute to hypercontractions, concomitant with augmented Ca 2ϩ mobilization in atherosclerotic vessels.…”
Section: Discussionmentioning
confidence: 79%
“…The Ca 2ϩ response induced by the native ligand 5-HT is likely to occur via activation of the recombinant 5-HT 1A receptor; no Ca 2ϩ signal could be detected in nontransfected CHO-K1 cells, although the Ca 2ϩ pathway was adequately responsive to bradykinin. CHO cells have previously been reported to express endogenous 5-HT 1B receptors, which are negatively coupled to adenylyl cyclase and positively coupled to increases in intracellular Ca 2ϩ formation (Dickenson and Hill, 1995;Giles et al, 1996). In the present study, the selective 5-HT 1B receptor antagonist SB 224289 (Gaster et al, 1998) affected the 5-HT-mediated Ca 2ϩ response little, if at all, whereas the selective 5-HT 1A receptor antagonist WAY 100635 (Fletcher et al, 1996) (Fargin et al, 1991), this may be different for CHO-K1 and C6-glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-HT 7A coupling to adenylyl cyclases occurs independent of G i . Several other G protein-linked members of the 5-HT receptor family, including 5-HT 1A , 5-HT 1D , 5-HT 1F , 5-HT 2C , and 5-HT 4 couple to increases in calcium (54 -58), and endogenously expressed 5-HT 1B and 5-HT 2B receptors increase intracellular calcium independent of phosphoinositide turnover (59,60).…”
Section: -Ht 7a Increases Intracellular Ca 2ϩmentioning
confidence: 99%